Development of new attenuation equation for subduction mechanisms in Malaysia water - Nazir, Ramli (Springer Verlag, 2016)
The attenuation equation for far field earthquake is important because the earthquake occurring in neighboring countries can be felt in Malaysia. In this study, a new attenuation was generated using the regression method. It was developed to calculate the peak ground acceleration (PGA) onsite (offshore platform). The database consisting of more than 150 PGAs from 9 events of earthquakes recorded by the Seismology Station in Malaysia was used to develop the relationship. In addition, attenuation relationships for subduction mechanisms from previous researchers are then compared with the newly generated ones in this research. The new attenuation equation was also validated and used to calculate the acceleration for far field earthquake in a case study of offshore platform at a Terengganu seaside. The result of PGA from the new generated attenuation relationship was in a good match with previous attenuation equations.